A Single Case Study of Speaking Anxiety in an Indonesian EFL Student: A Narrative Inquiry - Fitriani Nurhalimah; Aip Syaepul Uyun (Sapientia Humana: Jurnal Sosial Humaniora, 2026)
Speaking anxiety is one of the most common affective factors influencing English as a Foreign Language (EFL) learners' oral communication. This study aims to explore the lived experience of speaking anxiety in an Indonesian EFL student and to identify the factors shaping this experience. Employing a qualitative research design, this study adopted a single case study with a narrative inquiry approach to gain an in-depth understanding of the participant's personal story. The participant was an Indonesian EFL university student who experienced persistent anxiety when speaking English. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis to identify recurring patterns and meanings within the participant's narrative. The findings showed that the participant's teacher initially perceived her as lacking confidence during speaking activities. Further exploration revealed that her speaking anxiety was closely connected to repeated bullying experiences during junior high school, which damaged her self-confidence and led to a persistent fear of making mistakes and being negatively evaluated by others. These experiences continued to affect her willingness to communicate in English. The study emphasizes the importance of recognizing learners' personal histories and creating psychologically safe, empathetic classroom environments to reduce speaking anxiety and promote confidence in EFL learning.